The Individual Variations in Sperm Quality of High-Fertility Boars Impact the Offspring Production and Early Physiological Functions - Santa María Toledo-Guardiola; Chiara Luongo; Felipe Martínez-Pastor; Cristina Soriano-Úbeda; Carmen Matás (Veterinary Sciences, 2025)
Artificial insemination (AI) is essential in intensive pig production, which significantly depends on semen quality from boars selected for health, genetics, and fertility. While AI aims to improve productivity, larger litters often result in smaller and less resistant piglets. Beyond fertility and genetic traits, boars also influence offspring health. This study investigated the relationship between sperm parameters of highly fertile boars and both reproductive outcomes and piglet physiological indicators. Multivariate analysis revealed significant paternal effects on blood markers reflecting organ function, including those of the pancreas, liver, and kidneys, as well as on glucose homeostasis, lipid metabolism, oxidative stress, protein and carbohydrate metabolism, muscle contraction, and neural signaling. Notably, sperm velocity was correlated with mitochondrial function, which is crucial for sperm motility, capacitation, DNA integrity, and embryo development—factors likely linked to healthier, more resilient offspring. Boars transmitting superior sperm velocity, erythropoiesis efficiency, and oxygen transport capacities produced piglets with better glucose regulation, growth, and resistance to neonatal hypoglycemia. These findings underscore the broader impact of sperm quality on offspring vitality and suggest that advanced sperm analysis could improve boar selection and enable more effective, health-oriented breeding strategies.